The study of the body`s center of gravity in shot-putters - Vodickova, S. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2003)
The aim of this study was to find some limiting factors in the performance of shot putting with an emphasis on the kinematic parameters of the center of gravity. We used a noninvasive kinematographic method, which enabled us to perform a 3-D analysis of the movements of different athletes. On the basis of this study, factors of performance were determined (as opposed to the factors resulting from the formula for the distance of oblique throwing) and also the speed of the body`s center of gravity and extension of movement in a vertical line. Our results should lead to the optimization of training processes.